Association between the weight-adjusted waist index and the odds of type 2 diabetes mellitus in United States adults: a cross-sectional study - Zheng, Dongdong; Zhao, Suzhen; Luo, Dan; Lu, Feng; Ruan, Zhishen; Dong, Xiaokang; Chen, Wenjing (Frontiers in Endocrinology, 2024)
Abstract OBJECTIVE: To examine the association between the weight-adjusted waist index (WWI) and the odds of type 2 diabetes mellitus（T2DM）among U.S. adults. METHODS: Data from the National Health and Nutrition Examination Survey (NHANES) spanning six years (2007-2018) were utilized, encompassing 31001 eligible participants. Weighted multivariate logistic regression models and smoothed fit curves were employed to assess the association between WWI and the odds of T2DM, as well as dose-response relationships in the overall population and the odds of T2DM in various subgroups. RESULTS: In the fully adjusted continuous model, each one-unit increase in WWI was associated with a 1.14-fold increase in the odds of T2DM within the entire study population (2.14 [1.98,2.31], P < 0.0001). In the fully adjusted categorical model, when using the lowest tertile of WWI (T1) as the reference group, the second tertile (T2) and the third tertile (T3) were associated with a 0.88-fold (1.88 [1.64,2.17], P < 0.0001) and a 2.63-fold (3.63 [3.11,4.23], P < 0.0001) increase in the odds of T2DM. These findings indicated a positive correlation between WWI values and the odds of T2DM, aligning with the results of the smoothed-fitted curves. In the analysis of subgroups, in addition to maintaining consistency with the overall population results, we found interactions between age and hypertension subgroups. CONCLUSION: In conclusion, WWI was found to be positively associated with the odds of T2DM in U.S. adults.